Mercury and halogen emissions from Masaya and Telica volcanoes, Nicaragua - Witt, M; Mather, T; Pyle, D; Aiuppa, A; Bagnato, E; Tsanev, V (2008)
We report measurements of Hg, SO2, and halogens (HCl, HBr, HI) in volcanic gases from Masaya volcano, Nicaragua, and gaseous SO2 and halogens from Telica volcano, Nicaragua. Mercury measurements were made with a Lumex 915+ portable mercury vapor analyzer and gold traps, while halogens, CO2 and S species were monitored with a portable multi gas sensor and filter packs. Lumex Hg concentrations in the plume were consistently above background and ranged up to 350 ng m-3. Hg/SO2 mass ratios measured with the real-time instruments ranged from 1.1 × 10-7 to 3.5 × 10-5 (mean 2 × 10-5). Total gaseous mercury (TGM) concentrations measured by gold trap ranged from 100 to 225 ng m-3. Reactive gaseous mercury accounted for 1% of TGM, while particulate mercury was 5% of the TGM. Field measurements of Masaya's SO2 flux, combined with the Hg/SO2 ratio, indicate a Hg flux from Masaya of 7.2 Mg a-1. At Masaya's low temperature famaroles, Hg/CO2 mass ratios were consistently around 2 × 10-8, lower than observed in the main vent (Hg/C02 ∼ 10-7). Low-temperature fumarole Hg fluxes from Masaya are insignificant (∼150 g a-1). Ratios of S, C and halogen species were also measured at Masaya and Telica volcanoes. CO2/ SO2 ratios at Masaya ranged from 2.8 to 3.9, comparable to previously published values. At Masaya molar Br/SO2 was 3 × 10-4 and I/SO2 was 2 × 10-5, suggesting fluxes of 0.2-0.5 Mg HBr d-1 and 0.02-0.05 Mg HI d-1. At Telica the Br/SO2 ratio was also 3 × 10-4 and the I/SO2 ratio was 5.8 × 10-5, with corresponding fluxes of 0.2 Mg HBr d-1 and 0.06 Mg HI d-1. Gases at both volcanoes are enriched in I relative to Br and Cl, compared to gases from volcanoes elsewhere. Copyright 2008 by the American Geophysical Union.